Muslim 357 (Manila Aquarius Records & Tapes)
This film featured an undercover agent Lt. Jamal Rasul portrayed by Fernando Poe Jr. His assignment is to search the mastermind of the biggest syndicate in the city. The task is tough for a Muslim like him and its even tougher if the enemies and their illegal jobs are being protected by few but powerful authorities in the same group he belongs. What if the person he is looking for is also following him? ... with his magnum 375 as his weapon, which way should he goes?
VCD
Music by Alex M. Suniga, directed by Ronwaldo Reyes.
Fernando Poe, Jr., Eddie Garcia, Vivian Foz, Ruel Vernal.
Keywords: Feature films--Phils.